2011
DOI: 10.1074/jbc.m111.297283
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Translation Initiation of Non-long Terminal Repeat Retrotransposons by Hepatitis Delta Virus (HDV)-like Self-cleaving Ribozymes

Abstract: Background: HDV-like ribozymes map to several non-LTR retrotransposons, although their roles are not fully understood. Results: Self-cleaving ribozymes are found widespread in retrotransposons and promote translation initiation in vitro and in vivo. Conclusion: Ribozymes process many non-LTRs and facilitate translation of their ORFs. Significance: These new roles further explain the retrotransposon cycle and expand the functions of catalytic RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 72 publications
(86 reference statements)
7
92
0
Order By: Relevance
“…This similarity between the R2 and drz-Agam-2 family of sequences also renders the R2 ribozymes readily identifiable in sequence-and structurebased searches using the drz-Agam-2 core. 126 Sequence analysis of the ribozyme-containing regions of R2 elements revealed that areas of conservation among isolates map to the conserved core portions of the ribozyme such as the L3 and J4/2 segments, whereas divergent sequences are found in the variable portions of the ribozymes, and covariation is present between nucleotides that would form the base-paired helices in the folded RNA structure. Thus, a consensus sequence can be constructed in which the P3, P1.1, L3, and J4/2 portions of the ribozymes are identical, the J1/2 region varies in both length and composition, and the P1 and P4 helices contain mutations that maintain base pairing (Fig 4.8).…”
Section: R2 Ribozymesmentioning
confidence: 99%
See 3 more Smart Citations
“…This similarity between the R2 and drz-Agam-2 family of sequences also renders the R2 ribozymes readily identifiable in sequence-and structurebased searches using the drz-Agam-2 core. 126 Sequence analysis of the ribozyme-containing regions of R2 elements revealed that areas of conservation among isolates map to the conserved core portions of the ribozyme such as the L3 and J4/2 segments, whereas divergent sequences are found in the variable portions of the ribozymes, and covariation is present between nucleotides that would form the base-paired helices in the folded RNA structure. Thus, a consensus sequence can be constructed in which the P3, P1.1, L3, and J4/2 portions of the ribozymes are identical, the J1/2 region varies in both length and composition, and the P1 and P4 helices contain mutations that maintain base pairing (Fig 4.8).…”
Section: R2 Ribozymesmentioning
confidence: 99%
“…126 In addition to the R2 ribozymes in Drosophila, the R2 elements of the termites Kalotermes flavicollis and Reticulitermes lucifugus, 129 the sea squirt Ciona intestinalis, 130 the black-legged tick Ixodes scapularis (GenBank™ accession ABJB010506112), the horseshoe shrimp Triops cancriformis (GenBank™ accession EU854578), and the Zebra finch Taeniopygia guttata 131 were all found to harbor HDV-like ribozymes in their 5 0 terminal region. Other rDNA-associated retrotransposons with ribozymes include the R4 element 132 in the human intestinal roundworm Ascaris lumbricoides, the horse intestinal roundworm Parascaris equorum, and the R6Ag1 and R6Ag3 elements in A. gambiae.…”
Section: Additional Rt-associated Ribozymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Like the HHR, self-cleaving HDVlike ribozymes have been recently found widespread in genomes from all life kingdoms and usually associated with autonomous LINE retroelements (Webb et al , 2009 ;Eickbush and Eickbush , 2010 ;Ruminski et al , 2011 ). In mammals, however, only one example of HDV-like ribozyme has been described and, similarly to the amniota HHRs, specifically conserved in a large intron ( ~ 47 kb) of the CPEB3 (cytoplasmic polyadenylation element binding protein 3) gene of most mammalian genomes.…”
Section: Intronic Ribozymes Snrnas and Pre-mrna Splicingmentioning
confidence: 99%